Smart Farming for Poultry: Leveraging Chicken Raising with Low-Cost IoT-based Information Systems - Hanau, Carla; Lopes, Vinícius; Santos, Mateus; Oliveira, Roberto; Graciano-Neto, Valdemar V.; Kassab, Mohamad; David, José Maria N.; Braga, Regina (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2025)
Context: Brazil is among the most influential global poultry meat production countries. Occupying second place among the world’s largest producers, Brazil is the first in the export ranking. Hence, to meet the high demand, the market depends on the high productivity and performance of the birds produced. Problem: As a tropical country, production faces difficulties due to the birds’ sensitivity to fluctuations in environmental factors, such as temperature and relative humidity. These and other factors can lead to loss of production and low profitability. Proposed Solution: This paper investigates the impact of a low-cost IoT-based Information System (IS) for autonomous environmental regulation in poultry farming. Information Systems Theory: We conduct this research under the positivism umbrella, while still conceiving the solution under the General Systems Theory. Method: We conducted a classical controlled experiment. We used free-range chicken breed Label Rouge and Gallus Domesticus, separating them into intervention environment (under climate monitoring and regulation) and control environment (without monitoring/regulation). We considered the following variables for data analysis: weight gain, feed consumption and mortality. Student’s t test was applied. Summary of Results: The results showed a significant gain in the Label Rouge free-range chickens breed in the fifth week of evaluation, with the monitored chickens obtaining an average weight of 25% greater than those not monitored. Contributions and Impact in the IS area: The contributions of this research can be considered twofold: prescriptive, with the proposal of a low-cost IoT-based IS architecture for autonomous environmental regulation in poultry farming; and descriptive, with an empirical study being conducted and the results being reported. We conclude that the system’s automation can significantly reduce the need for manual monitoring, offering substantial labor savings and operational efficiency, especially advantageous for small-scale poultry producers.